Response to Frierson’s “Kantian Feeling: Empirical Psychology, Transcendental Critique and Phenomenology” - Grenberg, Jeanine (Con-Textos Kantianos. International Journal of Philosophy, 2016)
In this paper, I reject Frierson’s interpretation of Kantian reductionist phenomenology. I diagnose his failure to articulate a more robust notion of phenomenology in Kant as traceable to a misguided effort to protect pure reason from the undue influence of sensibility. But in fact Kant himself relies regularly on a phenomenological and felt first personal perspective in his practical philosophy. Once we think more broadly about what Frierson calls “the space of reasons,” we must admit a robust role for attentive reflection upon felt, phenomenological experience at the center of Kantian practical deliberation.
Keywords: Phenomenology; Attention; Moral Feeling of Respect; First-Personal